Inovasi Sistem Pegelolaan Bank Sampah Untuk Mendukung Desa Wisata Berbasis Lingkungan : Studi Kasus Desa Sukunan Gamping Sleman - Widianti, Emma (Indonesian Research Journal on Education, 2025)
Waste management is a strategic national and global issue, particularly for areas located at the intersection of domestic, commercial, and tourism activities. Sukunan Village, located in Gamping Sub-district, Sleman Regency, is one of the villages that has successfully developed an independent and innovative waste management system since 2003. This study aims to comprehensively analyze innovations in the waste bank management system in supporting the development of Sukunan Tourism Village as an environmentally based tourism village.This research employed a qualitative approach using a descriptive-analytical method. Data were collected through field observations, in-depth interviews with tourism village managers, waste bank administrators/change agents, community members, and visitors, as well as documentation review. Data analysis was conducted through data reduction, data display, and conclusion drawing, which were further strengthened by a SWOT analysis using the IFAS and EFAS matrices. Data validity was ensured through source and method triangulation.The results of the SWOT analysis indicate that the waste bank management system in Sukunan Village is positioned in Quadrant I, with IFAS and EFAS scores of 2.80 each. This position suggests that the most appropriate strategy for developing innovative waste bank management is a growth strategy, emphasizing institutional strengthening, enhancement of human resource capacity, system digitalization, and the strengthening of partnership networks. Meanwhile, control strategies function to maintain system stability and sustainability through the management of economic, social, institutional, and environmental